Using the Electronic Educational Package of the Stress Management Program for the Mental Health and Job Performance of Intensive Care Unit Nurses in the Face of Patients with COVID-19 - bazghale, Milad; Ebrahimi , Hossein; Shariati , Esmail; Basirinezhad, Mohammd Hasan (Shahroud Journal of Medical Sciences, 2024)
Background: Due to nurses’ special job position, they are faced with a variety of illnesses and accidents in intensive care COVID-19 wards, which puts them in front of so many stresses that can cause anxiety and endanger their mental health. The study aimed to investigate the influence of the web-based stress management program on mental health and job performance of ICU nurses in the face of patients with COVID-19. Methods: This study was a Quasi-experimental one, with pre-test, and post-test plan without control group using the General Health Questionnaire (GHQ-28) and the ACHIVE Job Performance Questionnaire. The stress management program was prepared as a multimedia product, the program consisted of eight parts and the duration of each part was ten minutes. The significant level was set at 0.05. Results: Nurses' job performance improved significantly after two weeks from the distribution of the web-based package to the participants and e-mail following the package use and completion of the tasks also 95.6% of nurses had symptoms of anxiety and depression, which became 58.8% after the intervention. Conclusions: The web-based stress management program is useful for improving nurses' mental health and job performance during and after the pandemic.